Celebes Petang: News Program Production Mechanism on Local Televisions - Sonni, Alem Febri; Hidayatullah, Fauzan; Sudarmin, Sudarmin (School of Journalism, Faculty of Communication Sciences, Universitas Padjadjaran, 2025)
Celebes TV, one of the local television stations in Makassar, features news as its main program, Celebes Petang. News value is a consideration for journalists to cover what the informant has witnessed and been concerned about because the news becomes more interesting to watch. This research aimed to identify the process of the TV news production of Celebes Petang and all the people involved in the production program and to find out the understanding of Celebes TV journalists on the general criteria for reporting newsworthy events. This qualitative approach collected the data by observation, interviews, and documentation. This research showed that the production process of the news program Celebes Petang on Celebes TV follows the procedure of television programs. The production process starts when the news manager, producer, and reportage in chief observe the broadcasting materials or theme from any courtesy. During the meeting, the reporter and the staff are assigned by the director of reportage to cover the news. After that, the reporter writes the script based on the news. This script is used as the material in the dubbing process. The next stage is editing the news items and dubbing. The producer will correct the result of the editing process. The approved result was printed into the data form and sent to the server to be aired live to the viewers by a crew of the master control room.